Human capital risk and the firmsize wage premium - Danny Leung; Alexander Ueberfeldt (Bank of Canada, 2008)
Why do employed persons in large firms earn more than employed persons in small firms, even after controlling for observable characteristics? Complementary to previous results, this paper proposes a mechanism that gives an answer to this question. In the model, individuals accumulate human capital and are exposed to the risk of losing some of their human capital as they change jobs, voluntarily or involuntarily. The model, calibrated to the United States and Canada, accounts for one-third of the firmsize wage premium. Regarding the earnings gap between Canada and the United States, the model finds that it is solely due to differences in labor market uncertainty.
Keywords: J24; J31; 330; Economic models; Labour markets; Productivity; Arbeitsmarkt; Betriebsgröße; Lohnniveau; Humankapital; Produktivität; Kanada; USA